KERAGAAN AGRIBISNIS MELON (Cucumis melo L.) AWOT DI KELURAHAN TALANG KRAMAT KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN - Candra, Debi Leo; Sobri, Khaidir; Iswarini, Harniatun (Universitas Muhammadiyah Palembang, 2017)
The Performance of Agribisness Melon Awot in Kelurahan Talang Kramat Kecamatan Talang Kelapa Kabupaten Banyuasin. The purpose of this research was to determine the application of Performance of Agribisness Melon Awot in Kelurahan Talang Kramat Kecamatan Talang Kelapa Kabupaten Banyuasin. To determine the constraints Performance of agribisness Melon Awot in Kelurahan Talang Kramat Kecamatan Talang Kelapa Kabupaten Banyuasin. And to investigate the income Performance of Agribisness Melon Awot in Kelurahan Talang Kramat Kecamatan Talang Kelapa Kabupaten Banyuasin. This research was conducted in the District of Kramat Village Talang Kelapa Banyuasin. On January to March 2016. The research method in this study used a survey, for the methods of sampling the writer used the purposive sampling technique. In this study the writer used the observation and direct interview to the respondents who have been determined by using tools like questionnaire that has been prepared in advance for collecting the data. The management of data have done by using tabulation and then was analyzed by descriptive qualitative approach and descriptive analysis matematie. Results of this research addressing that, Melon Agribusiness Performance of Awot include: Subsystem Proviion of Means of Production, farming subsystems, marketing Subsystem. Sales activities melon fruit crops undertaken by farmers of melon by way of the consumer come directly to the location of the plantation. Melon farming in area Kelurahan Talang Kramat Kecamatan Talang Kelapa Kabupaten Banyuasin well worth the effort. Where the R / C obtained was 1.4, which means every additional Rp 1 which spent will give a reception at 1.4 with R / C more than one can say it’s profitable the farmers.